Universal Information Security Governance System: Organizational and Legal Principles - M. A. Hadi; M. N. Abdulredha (Journal of Digital Technologies and Law, 2025)
Objective: to develop universal organizational and legal principles for building an information security governance system that will allow each organization to create its own effective information security governance system, taking into account its unique business goals and tasks.Methods: the research integrates the key elements of information security governance, such as vision, strategy, goals, policies, standards, processes, and matrices. Vision and goals set the direction of an organization’s development; policies and standards provide a conceptual framework for information protection; processes allow for systematic achievement of objectives; and matrices provide tools for evaluating and monitoring the entire structure. The proposed principles are consistent with international standards, regulatory requirements, and best practices in the field of information security.Results: the research showed that the developed information security governance system allows for a clear distribution of roles and responsibilities among the employees, ensuring effective implementation of the governance system. The authors also analyzed the existing principles of information security, integrating them into a security strategy that meets the corporate goals. The proposed universal system complies with regulatory legal requirements and can be adapted for organizations of any scale and profile.Scientific novelty: the paper represents a practical approach to the implementation of an information security governance system based on the authors’ experience, international standards, control systems and legal acts. Unlike existing approaches, the proposed system is flexible and can be adapted to any organization, which makes it a universal tool for information security governance.Practical significance: the research provides a structured approach to creating a universal information security governance system that can be used by organizations lacking knowledge and resources to implement such initiatives. The authors propose a general structure that can be adapted depending on the organization’s assets, the employees’ training and awareness of information security issues. This makes the paper a valuable resource for professionals seeking to increase information security in their organizations.